Digital and Analog communication systems : as per AICTE - K Sam Shanmugam (New Delhi Wiley India Pvt Ltd, 2012)
The book gives a unified treatment of theoretical and practical aspects of digital and analog communication systems, with emphasis on digital communication systems. It integrates theory with design, keeping theoretical details to a minimum, with over 60 practical and worked examples illustrating real-life methods. The emphasis is mainly on deriving design equations that relate performance of functional blocks to design parameters. It illustrates how to tradeoff between power, bandwidth and equipment complexity while maintaining an acceptable quality of performance.
Keywords: General Electronics; Classification for communication engineering systems